Mechanical and toxicological effects of deep-sea mining sediment plumes on a habitat-forming cold-water octocoral - Carreiro-Silva, Marina; Martins, Inês; Riou, Virginie; Raimundo, Joana; Caetano, Miguel; Bettencourt, Raul; Rakka, Maria; Cerqueira, Teresa; Godinho, António; Morato, Telmo; Colaço, Ana (Frontiers in Marine Science, 2022)
Deep-sea mining activities are expected to impact deep-sea biota through the generation of sediment plumes that disperse across vast areas of the ocean. Benthic sessile suspension-feeding fauna, such as cold-water corals, may be particularly susceptible to increased suspended sediments. Here, we exposed the cold-water octocoral, Dentomuricea aff. meteor to suspended particles generated during potential mining activities in a four weeks experimental study. Corals were exposed to three experimental treatments: (1) control conditions (no added sediments); (2) suspended polymetallic sulphide (PMS) particles; (3) suspended quartz particles. The two-particle treatments were designed to distinguish between potential mechanical and toxicological effects of mining particles. PMS particles were obtained by grinding PMS inactive chimney rocks collected at the hydrothermal vent field Lucky Strike. Both particle types were delivered at a concentration of 25 mg L-1, but achieved suspended concentrations were 2-3 mg L-1 for the PMS and 15-18 mg L-1 for the quartz particles due to the different particle density. Results of the experiment revealed a significant increase in dissolved cobalt, copper and manganese concentrations in the PMS treatment, resulting from the oxidation of sulphides in contact with seawater. Negative effects of PMS exposure included a progressive loss in tissue condition with necrosis and bioaccumulation of copper in their tissues and skeletons and death of all coral nubbins by the end of the experiment. Physiological changes under PMS exposure, included increased respiration and ammonia excretion rates in corals after 13 days of exposure, indicating physiological stress and potential metabolic exhaustion. Changes in the cellular stress biomarkers and gene expression profiles were more pronounced in corals exposed to quartz particles, suggesting that the mechanical effect of particles although not causing measurable changes in the physiological functions of the coral, can still be detrimental to corals by eliciting cellular stress and immune responses. We hypothesize that the high mortality of corals recorded in the PMS treatment may have resulted from the combined and potentially synergistic mechanical and toxicological effects of the PMS particles. Given the highly sensitive nature of octocorals, marine protected areas, buffer areas or non-mining areas may be necessary to protect deep-sea coral communities.